Spectral fundus autofluorescence peak emission wavelength in ageing and AMD. Issue 6 (1st December 2021) - Schultz, Rowena; Schwanengel, Linda; Klemm, Matthias; Meller, Daniel; Hammer, Martin
ABSTRACT: Purpose: To investigate the spectral characteristics of fundus autofluorescence (FAF) in AMD patients and controls. Methods: Fundus autofluorescence spectral characteristics was described by the peak emission wavelength (PEW) of the spectra. Peak emission wavelength (PEW) was derived from the ratio of FAF recordings in two spectral channels at 500–560 nm and 560–720 nm by fluorescence lifetime imaging ophthalmoscopy. The ratio of FAF intensity in both channels was related to PEW by a calibration procedure. Peak emission wavelength (PEW) measurements were done in 44 young (mean age: 24.0 ± 3.8 years) and 18 elderly (mean age: 67.5 ± 10.2 years) healthy subjects as well as 63 patients with AMD (mean age: 74.0 ± 7.3 years) in each pixel of a 30° imaging field. The values were averaged over the central area, the inner and the outer ring of the ETDRS grid. Results: There was no significant difference between PEW in young and elderly controls. However, PEW was significantly shorter in AMD patients (ETDRS grid centre: 571 ± 26 nm versus 599 ± 17 nm for elderly controls, inner ring: 596 ± 17 nm versus 611 ± 11 nm, outer ring: 602 ± 16 nm versus 614 ± 11 nm). After a mean follow‐up time of 50.8 ± 10.8 months, the PEW in the patients decreased significantly by 9 ± 19 nm in the inner ring of the grid. Patients, showing progression to atrophic AMD in the follow up, had significantly (p ≤ 0.018) shorter PEW at baseline than non‐progressing patients. Conclusions: Peak emission wavelength (PEW) is related to AMD pathology and might be a diagnostic marker in AMD. Possibly, a short PEW can predict progression to retinal and/or pigment epithelium atrophy.